Nazam al durar fi tanasub al ayat wa al suwar - Burhanuddin Abi Al Hasan Ibrahim Bin Umar Al Baqa'i (Dar al Kutub Al 'Ilmiyyah, 2020)
wd,jil 1,c.1, jil 2,c.1, jil 3,c.1, jil 4,c.1, jil 5,c.1, jil 6,c.1, jil 7,c.1, jil 8,c.1